The Intoxication of Destruction in Theory, Culture and Media : A Philosophy of Expenditure after Georges Bataille - Stapleton, Erin K. (Book collections on Project MUSE., 2022)
This book examines the desire for, and intoxication with, destruction as it appears in cultural objects and representation, arguing that all cultural and aesthetic value is fundamentally predicated on its own fragility, as well as the living transience of those who make and encounter it. Beginning with a philosophy of expenditure after Georges Bataille, each chapter maps different operations of destruction in media and culture. These operations are expressed and located in representations of human extinction and explosive architecture, in the body and in sexuality, and in media and digital archives, which constitute a further destabilisation of the notion of destruction in the dynamic between aspirational immortality and material volatility embedded in the archival systems of digital cultures.